Vocational education and training and higher education in the transition countries - Masson, Jean-Raymond [Verfasser] (My University, 2009)
"This article considers the contrasting developments in the new Member States, namely the declining student participation in vocational training, and the marked increase in participation in higher education, as demonstrated by the latest Eurostat statistics. The reforms of the educational systems which are under way have led to an increase in the numbers undertaking general and higher education and to improvements in overall performances in secondary education. Nevertheless, the substantive reform of initial vocational training remains problematical, while shortages of skilled workers are being felt. However, the differentials in terms of earnings and job markets are such that they continue to encourage the rejection of vocational training and a flight to higher education. At the same time, developments in higher education primarily relate to courses of long duration and are accompanied by an increase in failure at school and graduate unemployment, while significant changes are taking place at post-secondary level calling for substantial development of short higher education courses. In this context, the messages of the World Bank proposing that vocational training should be moved to post-secondary level, and of the European Union calling for a relaunch of vocational education primarily through a closer link with higher education seem to be contradictory. Further reflection is called for, with a greater understanding of the diversity of the situations, in the context of implementation of the Copenhagen and Bologna processes." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 1.4 Hochschulbildung; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; I 2.2.2 Osteuropa; Berufsbildung; Hochschulbildung; Quote; Auszubildender; Student; Durchlässigkeit im Bildungssystem; Arbeitslosenquote; Einkommenshöhe; Bildungsniveau; Europäische Union; Osteuropa; Quantitative Angaben